Kiprah Pembelajaran Kiai Langghar di Madura - Baisuni, Baisuni; Gaffar, Abdul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
Kiai is a role model who has an important role in society. Apart from being an example, the kiai's gait is seen in maintaining the values ​​of learning Islamic Religious Education in every corner of the village called Langghar, with enthusiasm and consistency (istiqomah) in explaining the Islamic education system starting from teaching materials, methods and evaluations created for generations. successor of the nation who not only knows about Islam but is also directed to practice. The existence of the kiai and his Langghar have a mission in grounding religious understanding. The results of the study show that the scope of the use of teaching materials and methods of the kiai in Langghar varies, but they maintain the old teaching materials in the Qur'an learning process and the development of Islamic knowledge such as Al-Magdadi and ca'bacaan (Madura: teaching materials consisting of several Islamic Religious Education material which includes daily aqoid and fiqh) although there are already some who have used Amsilati accompanied by learning the yellow book. Second, in the teaching and learning process the kiai still use the sorogan, bandongan, memorization and lecture methods. This method is considered still effective in maintaining the values ​​of Islamic Religious Education (PAI). In terms of social legality, there is recognition, especially in the villages, that the kiai has a role as the founder and manager of a non-formal educational institution, namely Langghar, which is based on the kiai's personal experience while studying and gaining knowledge in a pesantren.